Directed holey and ordered g-C(3)N(4.5)nanosheets by a hard template nanocasting approach for sustainable visible-light hydrogen evolution with prominent quantum efficiency - Antil, Bindu; Ranjan, Ravi; Gopinath, Chinnakonda S.; Deka, Sasanka (Journal of Materials Chemistry A, 2020)
It is desirable yet challenging to synthesize a highly ordered holey carbon nitride material with excess nitrogen atoms for a sustainable solar H(2)evolution. Herein, we report the development of directed highly ordered nitrogen-rich honeycomb-like mesoporous carbon nitride nanosheets by using a novel synthetic approach for this purpose. The unique formation route, surface structure and charge carrier dynamics of the two dimensional holey nanosheets are comprehensively monitored and confirmed by SAXS, HRTEM, AFM, BET, XPS and TRPL analyses. Non-stoichiometric high nitrogen content mesoporous nanosheets with the final stoichiometry of g-C(3)N(4.5)acquiring a high specific surface area (382 m(2)g(-1)), remarkable pore size (7.2 nm) and sheet thickness similar to 5-6 nm are realized in this first report. This elegant material possesses unique low band-gap energy (2.42 eV). Remarkably, the as-synthesized g-C(3)N(4.5)NSs exhibit a record high photocatalytic H(2)evolution rate of 8180 mu mol g(-1)h(-1)under the present light irradiation (420 <=lambda <= 510 nm) condition. The apparent quantum efficiency is found to be as high as 27.14% at 420 nm and retains its photocatalytic activity for longer consecutive catalytic cycles. Bigger pore size and pore volume, and thin walls leading to shortening of the path length of exciton pairs, efficient charge separation and the prolonged average life time of the charge carriers, and lone electron pairs associated with the excess nitrogen content are found to be the reasons behind the excellent visible light driven water splitting reaction.

Design of Bi-functional mixed oxide electrodes for selective oxidative C-C cleavage of glycerol to formate and synchronized green hydrogen production - Saha, Arindam; Murugiah, Vasantharadevi; Ranjan, Ravi; Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Saha, Avisekh; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2024)
Alkaline water electrolysis is a mature method to produce green hydrogen; however, it suffers from significantly high cost as high overpotentials are required for the oxygen evolution reaction (OER). However, the OER could be avoided altogether by replacing it with kinetically favorable oxidation of abundantly available feedstock molecules at a significantly low potential to value-added product(s) together with green hydrogen generation. This is a potential method to address the high cost of green hydrogen production while converting waste to wealth. Herein, we report green, template-free hydrothermal synthesis of an electrochemically active NiCoMn mixed oxide (NCMO) electrocatalyst with multiple sites, porous structure, large surface area, and nanoneedle (NN) morphology deposited directly over Ni foam (NF). Sustainable electrocatalytic performance was demonstrated for 120 h in 0.2 M alkaline glycerol using chronoamperometry and chronopotentiometry. Highly selective formate production demonstrated an exclusive C-C cleavage with the present catalyst system. Oxides of individual metal-ions (Ni, Co, and Mn) and their bimetallic combination (NiCo, NiMn, and CoMn) exhibited lower activity and product selectivity than the trimetallic NCMO electrocatalyst. The membrane-free two-electrode electrolyzer setup with NCMO/NF at both the anode and cathode (NCMO/NF & Vert;NCMO/NF) requires 1.63 V to accomplish 100 mA cm-2 with 0.2 M glycerol, which is 296 mV less than that of 1 M KOH solution. High faradaic efficiency was observed for hydrogen (98%) with highly selective formate (90%) production. Electrocatalytic formate generation from an alkaline glycerol solution with NCMO is an energy-efficient and promising approach that also supplies carbon-negative green H2. NiCoMn oxide nanoneedles with a cactus-like morphology are shown as bifunctional electrocatalysts that selectively oxidize glycerol to HCOOH and concurrently produce H2.